RANLP 2017 - Recent Advances in Natural Language Processing Meet Deep Learning 2017
DOI: 10.26615/978-954-452-049-6_083
|View full text |Cite
|
Sign up to set email alerts
|

Idiom Type Identification with Smoothed Lexical Features and a Maximum Margin Classifier

Abstract: In our work we address limitations in the state-of-the-art in idiom type identification. We investigate different approaches for a lexical fixedness metric, a component of the state-of-the-art model. We also show that our Machine Learning based approach to the idiom type identification task achieves an F1-score of 0.85, an improvement of 11 points over the state-of-the-art.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…The literature on the task of automatic type identification of idioms, more specifically verb and noun idiomatic combinations (VNIC), illustrates the use of these standard model evaluation metrics. Most of the work in this field either uses accuracy (used by Fazly et al (2009)) or F-score (used by Muzny and Zettlemoyer (2013), Senaldi et al (2016), Salton et al (2017)) to compare model performance. These measures provide an appreciable sense of the reliability of a given model, which is why they are commonly used as evaluation metrics.…”
Section: Drawbacks Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the task of automatic type identification of idioms, more specifically verb and noun idiomatic combinations (VNIC), illustrates the use of these standard model evaluation metrics. Most of the work in this field either uses accuracy (used by Fazly et al (2009)) or F-score (used by Muzny and Zettlemoyer (2013), Senaldi et al (2016), Salton et al (2017)) to compare model performance. These measures provide an appreciable sense of the reliability of a given model, which is why they are commonly used as evaluation metrics.…”
Section: Drawbacks Withmentioning
confidence: 99%
“…For more details on the background of the models, refer toSalton et al (2017). The resulting dataset is published on GitHub as a freely available resource.…”
mentioning
confidence: 99%
“…Fazly et al (2009) distinguish between identifying whether an expression has an idiomatic sense (idiom type classification) and identifying whether a particular usage of an expression is idiomatic (idiom token classification), and focus their work on analysing the canonical form (lexical and syntactic) of idiomatic expressions. The related work on idiom token classification at a sentence level includes (Sporleder and Li, 2009;Li and Sporleder, 2010a,b;Peng and Feldman, 2017;Fazly et al, 2009;Salton et al, 2016Salton et al, , 2017. Of particular relevance is Salton et al (2016) which demonstrated that it is possible to train a generic (as distinct to expression specific) idiom token classifier using distributed sentence embeddings.…”
Section: Introductionmentioning
confidence: 99%
“…distinguish between identifying whether an expression has an idiomatic sense (idiom type classification) and identifying whether a particular usage of an expression is idiomatic (idiom token classification), and focus their work on analysing the canonical form (lexical and syntactic) of idiomatic expressions. The related work on idiom token classification at a sentence level includes (Sporleder and Li, 2009;Li and Sporleder, 2010a,b;Peng and Feldman, 2017;Salton et al, , 2017. Of particular relevance is which demonstrated that it is possible to train a generic (as distinct to expression specific) idiom token classifier using distributed sentence embeddings.…”
Section: Introductionmentioning
confidence: 99%